Let A = 2 + 3 + . . . + 2 3
Answer = A − p ( p ( p ( p ( 2 ) + 1 ) ) )
Hint : p ( 1 ) = 2 , p ( 3 ) = 5 , p ( 5 ) = 1 1 .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Bad question, I considered p ( x ) as the minimum value of the closest prime to 2 x , so
p ( 2 ) + 1 p ( p ( 2 ) + 1 ) p ( p ( p ( 2 ) + 1 ) ) p ( p ( p ( p ( 2 ) + 1 ) ) ) = = = = 3 + 1 = 4 p ( 4 ) = 7 p ( 7 ) = 1 3 p ( 1 3 ) = 2 3
So the answer can also be 1 0 0 − 2 3 = 7 7
this problem really tolled me up
Log in to reply
Shouldn't it be trolled me up?
Problem Loading...
Note Loading...
Set Loading...
Firstly, one notes that p ( n ) denotes the nth prime. So, p ( p ( p ( p ( 2 ) + 1 ) ) ) = 5 9 . The more difficult part is the sum. One obviously would think it is the sum of all integers from 2 to 23, but you discovered that it is wrong after submitting. One notes that this problem is about primes and suspect that it is the sum of all primes from 2 to 23, which gives 1 0 0 . So, the answer is 1 0 0 − 5 9 = 4 1 .